Option 1 : 2

**Given**:

(x + 1/x) = 2.

**Formula**

x^{3} + 1/x^{3} = (x + 1/x)^{3} – 3 × x × (1/x) × (x + 1/x)

**Calculation**:

According to the formula,

x^{3} + 1/x^{3} = (x + 1/x)^{3} – 3 × x × (1/x) × (x + 1/x)

⇒ x^{3} + 1/x^{3} = (2^{3}) – 3 × (2)

⇒ x^{3} + 1/x^{3} = 8 – 6

⇒ x^{3} + 1/x^{3} = 2

**∴ The value of x ^{3} + 1/x^{3} is 2.**

** Shortcut Trick**:

We can solve this question by the value-putting method.

If we put x = 1, It satisfies the relation (x + 1/x) = 2.

.So when putting x = 1, x^{3} + 1/x^{3} gives 2.